Mapping digital competencies in the business domain - an empirical workplace analysis using job advertisements - Philipp Schlottmann (Forum Neue Medien in der Lehre Austria, 2024)
The rapid development of digital technologies has revolutionized the way companies operate and conduct business. Organizations now require higher attention paid to digital competencies to leverage the usage of digital tools and platforms effectively, optimize processes, reach customers and stay ahead of competition. This study examines how digital competencies have changed in the ﬁeld of business administration to identify essential skills and knowledge required in today's corporational landscape. Text mining is used to extract digital skills from a vast dataset of 25,000 job advertisements in the business administration field. The resulting empirical data is analysed to derive profiles outlining the development of digital competencies in the business administration field. The study reveals two specific digital competencies in high demand: analytical evaluation utilizing various software tools and communication via social media. Competence requirements from the labour market can indicate the design of study programmes and the adaptation of teaching methods.